SOCIAL ENGINEERING STRATEGY FOR AGRO TOURISM BASED ON KUPS EMPOWERMENT AT LMDH RENGGANIS JEMBER - Baiq Lily Handayani; Marga Mandala; Intan Kartika Setyawati (UNEJ e-Proceeding, 2022)
Tourism development becomes one of the alternatives to develop the economy of the community at the village level. The potential of unique and interesting tourism, based on the potential of natural resources becomes an attraction. The problem of human resources becomes an obstacle in the development of tourism. The purpose of this paper is to narrate social engineering strategies in the development of KUPS-based tourism (Social Forestry Business Group). The research method uses qualitative methods, with a research setting in LMDH Rengganis Jember. Criteria-based informant determination technique with purposive technique, data collection method using in-depth interviews focus group discussion and observations. Test the validity of data using source and researcher triangulation techniques, as well as data analysis techniques using flow methods. The results of the study found that the people of Village already have a Durian Village tourist attraction, but no longer operate. This is due to improper management. Social engineering strategies are needed to re-develop that potential. There is a KUPS group that can become social engineering media. The process of social engineering is carried out through several stages, namely, situation mapping, network mapping, figure mapping, citizen facilitation, discourse accompaniment, institutional and structural formation, program formation and citizen participation and program evaluation. Keywords: Agro Wana Wisata, LMDH, Tourism, Empowerment, Social Engineering.